Investigation of the effect of characteristics of gascontaining suspensions on the parameters of the process of ultrasonic wave propagation - Morkun, Vladimir; Morkun, Natalia; Tron, Vitaliy; Hryshchenko, Svitlana (Eastern-European Journal of Enterprise Technologies, 2017)
In the course of present study, we have investigated patterns of connection between fluctuations in the number and size of particles, suspended in a fluid, and characteristics of the field of volumetric ultrasonic waves. The presence of particles of the solid phase and gas bubbles introduces certain features to the process of attenuation and scattering of ultrasonic wave energy. The scattering of waves on the solid phase particles becomes considerable when the wavelength is commensurate with the size of the particles themselves. In order to characterize the absorption and scattering of acoustic oscillations by oscillating gas bubbles, we applied the concepts of effective cross-sections of damping, absorption and scattering. The dependence is presented of the magnitude of cross-section of ultrasound damping by air bubbles on frequency of the sound wave. It was established that the magnitude of attenuation of volumetric ultrasonic oscillations of high frequency (≥5 MHz) in an actual pulp depends almost only on the concentration of the solid phase and particle size of the crushed material. The frequency of volumetric ultrasonic waves, at which the components of their absorption and scattering by particles of the solid phase in suspension are equal, characterizes the average particle size. A given frequency does not depend on the particle concentration and can be applied to estimate their mean size